Prospective Memory Impairment and Executive Dysfunction in Prefrontal Lobe Damaged Patients: Is There a Causal Relationship? - Giovanni A. Carlesimo; Margherita di Paola; Lucia Fadda; Carlo Caltagirone; Alberto Costa (Behavioural Neurology)
Background. The prospective memory (PM) construct is aimed at capturing cognitive operations involved in the successful accomplishment of delayed intentions. It is generally agreed that PM impairment occurs in patients with prefrontal lobes damage. Objective. To evaluate if there is a causal role of a deficit of executive abilities (failures of planning, set-shifting, selective attention, or working memory) over the PM impairment. Methods. We report a detailed investigation of PM and executive abilities in two patients with posttraumatic damage to prefrontal lobes who complained from a reduced compliance with appointments and daily routines. Results. Laboratory tests confirmed a difficulty in fulfilling delayed intentions in response to the occurrence of critical events and elapsed time. In one patient, PM impairment was associated with poor performance on tests investigating planning, working memory, and mental shifting. The other patient performed in the normal range on all executive tests. Conclusions. Despite the frequent claim of a dependence of PM deficits from executive dysfunction, the reported cases demonstrate that this is not necessarily the case. The results are discussed in the light of current hypotheses relating PM impairment to other deficits that commonly occur as a result of damage to the prefrontal lobes.